The Identification and Quantification of Phospholipids from Thermus and Meiothermus Bacteria. Issue 11 (10th September 2014) - Lagutin, Kirill; MacKenzie, Andrew; Houghton, Karen M.; Stott, Matthew B.; Vyssotski, Mikhail
Abstract: Structural identities of the major phospholipid (PL‐2), minor phospholipid (PL‐1) and trace phospholipid (PL‐0) from representative strains of the genera Thermus and Meiothermus were established. Phospholipids were quantified using phosphorus‐31 nuclear magnetic resonance ( 31 P‐NMR). The structures of the major phospholipid (PL‐2) from Thermus filiformis MOK14.7 and Meiothermus ruber WRG6.9 were identified as 2′‐ O ‐(1, 2‐diacyl‐ sn ‐glycero‐3‐phospho)‐3′‐ O ‐(α‐ N ‐acetylglucosaminyl)‐ N ‐glyceroyl alkylamine (GlcNAc‐PGAA) and 2′‐ O ‐(2‐acylalkyldiol‐1‐ O ‐phospho)‐3′‐ O ‐(α‐ N ‐acetylglucosaminyl)‐ N ‐glyceroyl alkylamine (GlcNAc‐diolPGAA). Interestingly, M. ruber contained only a diacyl form of GlcNAc‐PGAA (87 %), while T. filiformis contained both GlcNAc‐PGAA (59 %) and GlcNAc‐diolPGAA (18 %). The structures of the minor phospholipid (PL‐1) were established as 2′‐ O ‐(1, 2‐diacyl‐ sn ‐glycero‐3‐phospho)‐3′‐ O ‐(α‐glucosaminyl)‐ N ‐glyceroyl alkylamine (GlcN‐PGAA, 13 %) in T. filiformis and 2′‐ O ‐(1, 2‐diacyl‐ sn ‐glycero‐3‐phospho)‐3′‐ O ‐(α‐galactosaminyl)‐ N ‐glyceroyl alkylamine (GalN‐PGAA, 19 %) in M. ruber . This is the first reliable discovery of phosphatidylglyceroylalkylamines modified by glucosamine or galactosamine with a free amino group. No signs of diol‐based phosphatidylglyceroylalkylamines were found in PL‐1 phospholipids. Similar to PL‐2, trace phospholipid (PL‐0) from T. filiformis contained both unsubstituted diol‐based phosphatidylglyceroylalkylamine (diolPGAA) and PGAA, while M . ruber contained only free PGAA. Unlike analysis using TLC, the diol form of phosphatidylglyceroylalkylamines is clearly resolved from the diacyl form via 31 P‐NMR.